2017
DOI: 10.1111/pde.13281
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of pediatric morphea treatment by pediatric dermatologists

Abstract: Background/Objectives: Studies describing treatment efficacy in pediatric morphea

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…10 We only reviewed patients treated with systemic therapy, but may have seen a greater effect of publication of CTPs if we had compared how many patients were treated with topical monotherapy before and after publication, as previous studies have found that a significant proportion of dermatologists treat even linear morphea with only topical therapy. 24 Although not statistically significant, there was a decrease in the percentage of patients who were treated Our findings support that there was a standardization of treatment at our institution in treatment approach for patients with morphea requiring systemic therapy after the publication of the CTPs. In addition, our data showed a statistically significant shift in providers who were prescribing and recommending systemic treatment.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…10 We only reviewed patients treated with systemic therapy, but may have seen a greater effect of publication of CTPs if we had compared how many patients were treated with topical monotherapy before and after publication, as previous studies have found that a significant proportion of dermatologists treat even linear morphea with only topical therapy. 24 Although not statistically significant, there was a decrease in the percentage of patients who were treated Our findings support that there was a standardization of treatment at our institution in treatment approach for patients with morphea requiring systemic therapy after the publication of the CTPs. In addition, our data showed a statistically significant shift in providers who were prescribing and recommending systemic treatment.…”
Section: Discussionsupporting
confidence: 59%
“…For example, we did not have patients treated with alternative systemic therapies such as antibiotics or antimalarials as reported in prior studies . We only reviewed patients treated with systemic therapy, but may have seen a greater effect of publication of CTPs if we had compared how many patients were treated with topical monotherapy before and after publication, as previous studies have found that a significant proportion of dermatologists treat even linear morphea with only topical therapy . Although not statistically significant, there was a decrease in the percentage of patients who were treated with topical therapy prior to systemic medication in the post‐CTP group.…”
Section: Discussionmentioning
confidence: 99%
“…1 Pediatric rheumatologists overwhelmingly chose systemic immunosuppression as first-line therapy while a survey of pediatric dermatologists in the United States reported that 37% considered topical agents as primary therapy or monotherapy for LS of the head or neck. 8 The choice of immunosuppressive agent usually follows consensus treatment plans for juvenile LS: MTX as first-line systemic treatment and MMF as second-line treatment in refractory cases. 2 It is known that IL-6 promotes fibrosis and its inhibition in animal models of systemic sclerosis retarded progression and decreased the severity of cutaneous fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, early signs may be subtle, progression can be slow, and classic signs of disease damage can be prominent when morphea is still active. This complexity contributes to well-documented diagnostic discrepancies, treatment delays, and undertreatment . Unrecognized and untreated disease activity leads to accrual of permanent damage, correlating with poorer patient-reported quality of life (QoL) outcomes.…”
Section: Assessing Disease Activity In Morpheamentioning
confidence: 98%
“…Hence, deep tissue extension is a marker of disease severity, requiring more aggressive treatment interventions . Yet physician uncertainty regarding the meaning of atrophy in morphea and the challenges of measuring atrophy can contribute to deep tissue involvement being overlooked . The MAM attempts to address this important conundrum by including progressive atrophy in the past 6 months for assessment of linear morphea.…”
Section: Expanded Morphological Features To Accurately Capture Diseas...mentioning
confidence: 99%